The Dynamics of Legal Networks: State Attorney General Amicus Brief Coalition Formation. (3rd July 2018) - Gleason, Shane A.
ABSTRACT: State attorneys general, the second most frequent and successful class of amici at the Supreme Court, are more successful as coalition size increases. While a large literature examines their amicus activity, scholars know little about how their coalitions form. This presents an incomplete account as broad coalitions are possible only if they are first mobilized. Utilizing social network analysis, I argue attorney general amicus brief coalitions are the product of the broader context. This context is dynamic. In the 1980s and 1990s coalitions are predicted by resources. By the 2000s, an increasingly partisan environment makes ideological similarity the main predictor of coalition formation. These findings draw attention to not only the utility of network approaches to judicial politics, but also the importance of changes in the broader environment in how attorneys general and other actors are able to mobilize coalitions to advance their preferences at the Court.